Two-photon absorption generated by optically amplified signals - Donegan, John; Bradley, Louise; Kilper, Daniel (My University, 2008)
Two-photon absorption generated by band-limited amplified spontaneous emission noise was found to be twice that generated by a continuous-wave optical signal with the same average power. A simple formula for describing the two-photon absorption generated by optically amplified signals has been obtained and confirmed experimentally.
PUBLISHED
Keywords: band-limited amplified spontaneous emission noise continuous-wave optical signal optically amplified signals two-photon absorption; Nanoscience & Materials